Emodin Ameliorates LPS-Induced Acute Lung Injury, Involving the Inactivation of NF-κB in Mice - Min Xiao (International Journal of Molecular Sciences, 2014)
Acute lung injury (ALI) and its severe manifestation of acute respiratory distress syndrome (ARDS) are well-known illnesses. Uncontrolled and self-amplified pulmonary inflammation lies at the center of the pathology of this disease. Emodin, the bio-active coxund of herb Radix rhizoma Rhei, shows potent anti-inflammatory properties through inactivation of nuclear factor-κB (NF-κB). The aim of this study was to evaluate the effect of emodin on lipopolysaccharide (LPS)-induced ALI in mice, and its potential bio-mechanism. In our study, BALB/c mice were stimulated with LPS to induce ALI. After 72 h of LPS stimulation, pulmonary pathological changes, lung injury scores, pulmonary edema, myeloperoxidase (MPO) activity, total cells, neutrophils, macrophages, TNF-α, IL-6 and IL-1β in bronchoalveolar lavage fluid (BALF), and MCP-1 and E-selectin expression were notably attenuated by emodin in mice. Meanwhile, our data also revealed that emodin significantly inhibited the LPS-enhanced the phosphorylation of NF-κB p65 and NF-κB p65 DNA binding activity in lung. Our data indicates that emodin potently inhibits LPS-induced pulmonary inflammation, pulmonary edema and MCP-1 and E-selectin expression, and that these effects were very likely mediated by inactivation of NF-κB in mice. These results suggest a therapeutic potential of emodin as an anti-inflammatory agent for ALI/ARDS treatment.